2009
DOI: 10.1016/s0924-9338(09)71471-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Stress Level Among Medical School Students of Semnan University, Iran

Abstract: Background:The professional education can be stressful experience and medical students are exposed to high levels of stress in both theoretical and clinical components of their educational programme. The high level of stress often leads to disruptions in physiological and psychological health.Objective:The purpose of this study was to study stress in medical school students of Semnan university.Methods:This study was a descriptive and cross-sectional research. The sample were 211 students of general physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies have reported high level of stress particularly in students of medicine [5,19,39,40], dentistry [41], pharmacy [42], and physiotherapy [43] programs. The majority of students face high level of stress in the medical college [24,25,28]. In two earlier studies the overall prevalence of stress in medical students was found to be 41.9% [37] and 29.6% [35], respectively, and in Saudi Arabia the figure reported is 57% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported high level of stress particularly in students of medicine [5,19,39,40], dentistry [41], pharmacy [42], and physiotherapy [43] programs. The majority of students face high level of stress in the medical college [24,25,28]. In two earlier studies the overall prevalence of stress in medical students was found to be 41.9% [37] and 29.6% [35], respectively, and in Saudi Arabia the figure reported is 57% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that personality traits of medical students include being highly motivated and action oriented achievers, which helps them get high scores; yet same students cannot tolerate feelings of helplessness and dependency and therefore are more prone to stress or less capable of handling it [17,18]. Reports have shown association of high level of stress among medical students with different types of academic stressors [19][20][21][22][23][24][25][26][27]. Studies related to stress in medical education in Arab countries have also confirmed that stress, depression, and anxiety are common among medical students [6,28].…”
Section: Introductionmentioning
confidence: 99%
“…This is expected and can be related to the resources available in a developing country (Forster-Williams et al, 1996). Similar studies related to stress in medical education have also been carried out in Saudi Arabia, Australia, Iran, Egypt, Pakistan and Nepal (Abdulghani, 2008;Amr et al, 2008;Bineshian et al, 2009;Mouret, 2002;Sheikh et al, 2004;Sreeramareddy et al, 2007) Students studying in a foreign country have problems related to adjustment in the country. These include a new cultural environment, accommodation, finance, communication, disruption of social support and along with all this, adjustment with the medical school environment.…”
Section: Stress Among Medical Students Across the Worldmentioning
confidence: 70%
“…2,4,5 However, other yeasts and dermatophytes can also cause the disease. 3,6 Treatment of fungal infections in the ear includes careful cleaning of the ear canal and using a topical medicine, such as a 2 per cent salicylic acid solution in alcohol and 1-2 per cent acetic acid because the acidic environment prevents fungal growth. Ointments containing nystatin or mycostatin are usually used to treat candida infections.…”
Section: Introductionmentioning
confidence: 99%